2015
DOI: 10.1158/0008-5472.can-14-3547
|View full text |Cite
|
Sign up to set email alerts
|

The miR-146b-3p/PAX8/NIS Regulatory Circuit Modulates the Differentiation Phenotype and Function of Thyroid Cells during Carcinogenesis

Abstract: The presence of differentiated thyroid cells in thyroid cancer is critical for the antitumor response to radioactive iodide treatment, and loss of the differentiated phenotype is a key hallmark of iodide-refractory metastatic disease.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 51 publications
(59 reference statements)
3
84
0
4
Order By: Relevance
“…Antagonizing miR-146b in human thyroid cancer cells has been shown to reinduce NIS-mediated iodide uptake (41). Apart from NIS, miR-146b is predicted to repress other iodide-metabolizing proteins such as DEHAL and DIO2 (40). It happens that NIS, DEHAL, and (Fig.…”
Section: From Cancer Genes To Signaling and Differentiation: Toward Amentioning
confidence: 98%
See 1 more Smart Citation
“…Antagonizing miR-146b in human thyroid cancer cells has been shown to reinduce NIS-mediated iodide uptake (41). Apart from NIS, miR-146b is predicted to repress other iodide-metabolizing proteins such as DEHAL and DIO2 (40). It happens that NIS, DEHAL, and (Fig.…”
Section: From Cancer Genes To Signaling and Differentiation: Toward Amentioning
confidence: 98%
“…It has also been proven to be elevated in the serum of patients with PTC and some of its target genes have been validated in thyroid cancer (38,39). MiR-146b specifically represses PAX8 and NIS, two genes essential for determining the differentiate phenotype of thyroid cancer (40). Antagonizing miR-146b in human thyroid cancer cells has been shown to reinduce NIS-mediated iodide uptake (41).…”
Section: From Cancer Genes To Signaling and Differentiation: Toward Amentioning
confidence: 99%
“…Many patients with advanced thyroid cancer do not benefit from the radioiodine therapy due to the reduced expression and function of the Na C /I -symporter (NIS). It was shown that lowered levels of NIS in thyroid tumors are at least in part caused by the overexpression of miR-339 and miR-146b, and inhibition of these microRNAs results in the increased uptake of radioactive iodine by the thyroid cancer cells (68,69,70). Data obtained in the in vitro experiments provided the basis for a number of preclinical studies related to the modulation of microRNAs in PTC, currently performed mainly on mouse models.…”
Section: The Potential Of Micrornas In Thyroid Cancer Treatmentmentioning
confidence: 99%
“…Moreover, the differential expression of some of these and other miRNAs is associated with TC aggressiveness, epithelial-mesenchymal transition, vascular invasion, lymph node dissemination, risk of recurrence and dedifferentiation, including increased expression of miR-9, miR-21 and miR-146b, HMGB1-induced miR-221 and miR-222 upregulation and miR-204 downregulation (Braun et al 2010, Mardente et al 2012, Chou et al 2013, Cancer Genome Atlas Research Network 2014, Guo et al 2015, Sondermann et al 2015. By specifically downregulating hNIS expression, miR-339 and miR-146b are identified to promote TC dedifferentiation and RAI resistance (Lakshmanan et al 2015, Riesco-Eizaguirre et al 2015. Accordingly, inhibition of these miRNAs by specific inhibitors results in improved RAI sensitivity (Lakshmanan et al 2015, Li et al 2015, Riesco-Eizaguirre et al 2015.…”
Section: Transcriptional Regulation By Mirnasmentioning
confidence: 99%
“…By specifically downregulating hNIS expression, miR-339 and miR-146b are identified to promote TC dedifferentiation and RAI resistance (Lakshmanan et al 2015, Riesco-Eizaguirre et al 2015. Accordingly, inhibition of these miRNAs by specific inhibitors results in improved RAI sensitivity (Lakshmanan et al 2015, Li et al 2015, Riesco-Eizaguirre et al 2015. All together, miRNA dysregulation in TC provides mechanistic insights into TC development and progression and represents potential targets for improving TC diagnostics, prognosis and therapy.…”
Section: Transcriptional Regulation By Mirnasmentioning
confidence: 99%